68 APOLIPOPROTEIN E POLYMORPHISM MODULATES THE ASSOCIATIONS OF OBESITY AND INSULIN RESISTANCE WITH C-REACTIVE PROTEIN IN YOUNG ADULTS: THE BOGALUSA HEART STUDY. Issue 1 (1st January 2007) - Patel, D. A.; Srinivasan, S. R.; Xu, J.; Chen, W.; Boerwinkle, E.; Berenson, G. S.
Abstract : Background: Apolipoprotein (apo E) polymorphism is known to exert pleiotropic effects on several physiologic processes besides lipoprotein metabolism. Although apo E genotype is known to modulate C-reactive protein (CRP) levels, its influence on the association of obesity and insulin resistance with CRP is not known. Methods: This aspect was examined in a biracial (black-white) community-based sample of 929 young adults (mean age 32.8 years, 72% whites, 44% males) who had data on apo E genotype and plasma CRP levels along with other cardiovascular risk factor variables. Results: The frequencies of the e2, e3, and e4 alleles differed significantly between whites and blacks (0.079, 0.770, and 0.151 for whites; 0.187, 0.656, and 0.227 for blacks). Age-, race-, and gender-adjusted mean value of CRP differed among apo E genotype groups [apo E4 (E4/4 and E4/3) < apo E2 (E2/2 and E3/2) or apo E3 (E3/3), p = .03-.001]. In multivariate analysis, significant interaction effects of genotype with race, body mass index (BMI), and insulin resistance index (HOMA-IR) on CRP levels were noted. Significant race difference (black > white, p = .02-.03) in CRP levels were observed only in apo E2 and apo E4. Further, within each genotype group, both BMI and HOMA-IR showed significant positive associations with CRP levels. However, the magnitude of these associations was least in the E4 group compared with the E2 or E3 group. Conclusion: The associations of CRP with obesity and insulin resistance were attenuated in the E4 genotype compared with the E2 or E3 genotype.